Study of bacterial infection and antimicrobial sensitivity pattern in diabetic foot lesion - Akhter, Shameem; Asna, Shah Md Zahurul Haque; Rahman, M Mushfequr; Hafez, MA (Bangladesh Journal of Medical Microbiology, 2012)
A cross sectional study was carried out on patients with diabetic foot lesions to determine the spectrum of aerobic microbial flora and to determine the microbial pathogens of the diabetic foot lesions and their antimicrobial sensitivity pattern. A total of 226 organisms were isolated from 218 patients and polymicrobial infection was found in 3.7 % cases. Age of the study population ranged from 20 - >80 yrs of which most of the patients were from 40 to 70 yrs (81 %). Male female ratio was= 3:1. In this study, Pseudomonas sp. (22.1 %), Proteus mirabilis (16.4 %) and S. aureus (14.6 %) were the predominant organisms isolated. Antimicrobial susceptibility pattern of the isolates were done in which imipenem and ciprofloxacin were found to be the most effective against all organisms. DOI: http://dx.doi.org/10.3329/bjmm.v6i2.19372 Bangladesh J Med Microbiol 2012; 06(02): 20-23